2018
DOI: 10.14715/cmb/2018.64.6.15
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of microRNA-17 as a potential biomarker in diagnosis of colorectal cancer

Abstract: This meta-analysis was aimed to determine the diagnostic accuracy of circulating microRNA-17 for colorectal Cancer (CRC). Databases including PubMed, Embase, Web of Science, Cochrane Library and China National Knowledge Infrastructure (CNKI) were searched up to February 23, 2018 for eligible studies. Quality Assessment of Diagnostic Accuracy Studies (QUADAS) was employed to assess the quality of the included studies. Meta-analysis was performed in STATA 13.0. Ten studies with total 938 CRC patients and 638 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Prior studies in sepsis have demonstrated similar findings with lower levels of microRNAs (miR-23a-5p, miR-26a-5p, miR-26b-5p, miR-103a-3p, miR-150-5p) in septic patients compared with healthy controls; however, systemic levels of these cellular microRNAs were increased in patients with severe sepsis or sepsis mortality. 16,20,37,41,42 Given the concurrent findings between PtPs in our study and sepsis studies, these microRNAs may yield early predictive value for trauma patients at risk for infectious complications and poor outcomes in trauma. Further evaluation of miR-103a-3p as a marker of VTE is merited given that the association between elevated levels of miR-103a-3p and VTE has been previously described in patients with recurrent VTE and potential mechanisms of action have been proposed.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Prior studies in sepsis have demonstrated similar findings with lower levels of microRNAs (miR-23a-5p, miR-26a-5p, miR-26b-5p, miR-103a-3p, miR-150-5p) in septic patients compared with healthy controls; however, systemic levels of these cellular microRNAs were increased in patients with severe sepsis or sepsis mortality. 16,20,37,41,42 Given the concurrent findings between PtPs in our study and sepsis studies, these microRNAs may yield early predictive value for trauma patients at risk for infectious complications and poor outcomes in trauma. Further evaluation of miR-103a-3p as a marker of VTE is merited given that the association between elevated levels of miR-103a-3p and VTE has been previously described in patients with recurrent VTE and potential mechanisms of action have been proposed.…”
Section: Discussionmentioning
confidence: 56%
“…Similar to miR-21-3p, these individual microRNAs affect multiple signaling pathways in the inflammatory response and include suppression of PTEN (miR23a-5p, miR-26a-5p, miR-92a-3p), NF-κB (miR-16-5p, miR23a-5p), TLR signaling (miR-16-5p, miR-92a-3p, miR-103a-3p), STAT3 (miR-223-3p), T-cell activation (miR-16-5p, miR-103a-3p, miR-150-5p), and apoptosis (miR-16-5p, miR23a-5p). 18,[35][36][37][38][39][40] Patients with uncomplicated recovery demonstrated more significant early suppression of these microRNAs, suggesting that the early inflammatory response to trauma includes downregulation of microRNAs that suppress immune signaling. By contrast, patients with complicated recovery had microRNAs levels closer to healthy controls suggesting limited suppression of these microRNAs, which may, at later time points, be consistent with subsequent immune dysregulation associated with complicated recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the miRNA-17/92a cluster were found elevated in plasma samples collected from patients with CRC and precancerous lesions in multiple studies [ 103 , 104 , 105 ]. A vast meta-analysis, including more than 900 CRC patients and 638 healthy controls, proved that miRNA-17 could identify CRC cases with satisfying accuracy [ 106 ]. Furthermore, the diagnostic value of miRNA-17 was confirmed by another study set to verify the accuracy of a panel formed by eight plasma miRNAs in recognizing CR adenomas [ 107 ].…”
Section: Liquid Biopsymentioning
confidence: 99%
“…miR-92 marker specifically differentiates CRC from gastric cancer markers, making it to more sensitive CRC marker [ 152 ]. Similarly, a meta-analysis observed an increase in miR-17 in plasma/serum/faecal levels of CRC patients, with 68% specificity [ 156 ]. miR-92a together with miR-21 was highly increased in serum samples, possessing prognostic value in CRC patients [ 156 ].…”
Section: Cell-free Nucleic Acids In Cancer Managementmentioning
confidence: 99%
“…Similarly, a meta-analysis observed an increase in miR-17 in plasma/serum/faecal levels of CRC patients, with 68% specificity [ 156 ]. miR-92a together with miR-21 was highly increased in serum samples, possessing prognostic value in CRC patients [ 156 ]. Further, results from the analysis of CRC patient plasma revealed significant upregulation of a miRNA panel (miR-15b, miR-18a, miR-19a, miR-19b, miR-29a and miR-335) depicting different miRNA expression patterns amongst CRC patients and healthy subjects [ 91 ].…”
Section: Cell-free Nucleic Acids In Cancer Managementmentioning
confidence: 99%